Modeling and collision avoidance control for the Disturbance-Free Payload spacecraft - Yang, Hongjie; Liu, Lei; Yun, Hai; Li, Xinguo (Acta astronautica, 2019)
The Disturbance-Free Payload (DFP) spacecraft, which includes the payload module (PM) and the support module (SM) connecting through voice coil motors (VCM), can provide unprecedented control and motion stability for the sensitive payload. The payload module and the support module have a high collision probability because of close proximity formation. In order to perform collision avoidance control on two modules, this paper establishes the dynamics model of the DFP spacecraft and proposes a collision avoidance control strategy based on the model predictive control (MPC). The established model synthesizes the back-Electromotive-Force (back-EMF) of the VCM and the stiffness and damping of the flexible cables. The MPC controller converts the collision avoidance problem into a quadratic programming problem. The control forces are obtained by solving the quadratic programming problem. The collision avoidance control simulation of the DFP spacecraft has performed while the payload module subjects to sudden disturbance. The simulation results verify the effectiveness of the proposed control strategy and show that the proposed MPC controller exhibits better collision avoidance capability than that of the PD controller. •An MPC controller is proposed for the DFP spacecraft to avoid collisions.•The dynamics model synthesizes the back-EMF of the VCM, the stiffness and the damping of the flexible cables.•The simulation studies of collision avoidance are provided.•The collision avoidance capability of the MPC controller is compared with that of PD controller.